How does networking impact the SMEs growth - Širec, Karin (Organizacija (Kranj), 2009)
Today''s market conditions are forcing companies to adapt to changes in order to survive, grow and be competitive. Such changes include inter-company cooperation and networks, which allow for competition and innovation in a dynamic environment. Today, almost all industries are affected by the evolution of networking relationships within and between firms; however, previous studies have revealed that companies differ in their competitive strategies, strategic and technological orientation, and methods of networking. Most of these studies have linked networking with performance, with less empirical evidence on linking networking in SMEs with company growth. Previous research has also shown that entrepreneurial potential in Slovenia is not fully utilized. For this reason, the presented paper investigates a networking in SMEs and its contribution to the companies'' growth.
Keywords: podjetništvo; mala podjetja; srednja podjetja; poslovno sodelovanje; konkurenčnost; razvoj